Home advantage during the COVID-19 pandemic in European football - McCarrick, D.; Bilalic, M.; Neave, N.; Wolfson, S. (Psychology of Sport and Exercise, 2021)
The home advantage (HA) is a robust phenomenon in soccer whereby the home team wins more games and scores more goals than the away team. One explanation is that the home crowd spurs on home team performance and causes the referee to unconsciously favour the home team. The Covid-19 pandemic provided a unique opportunity to assess this explanation for HA, as European soccer leagues played part of the 2019/2020 season with crowds present and concluded with crowds absent. Using multi-level modelling we compared team performance and referee decisions pre-Covid (crowd present) and post-Covid (crowd absent) across 9,528 games from 15 leagues in 11 countries. HA (goals scored and points gained) was significantly reduced post pandemic, which reflected the inferior performance of the home team. In addition, referees awarded significantly fewer sanctions against the away teams, and home teams created significantly fewer attacking opportunities when they played without fans.